MANAGEMENT OF TORTIOUS LIABILITY OF TRESPASS TO PERSON AND ADMINISTRATIVE EFFECTIVENESS IN STATE OWNED TERTIARY EDUCATIONAL INSTITUTIONS IN BORNO STATE, NIGERIA - MUSA, ABUBAKAR; MANGA, SANI DANTANI (Sokoto Educational Review, 2023)
Achievement of educational goals necessitates a conducive teaching and learning environment for both teachers and students, which is impossible to achieve without effective tort liability management in schools. This study investigated the relationship between management of tort of trespass to person and administrative effectiveness in state owned tertiary educational institutions in Borno State, Nigeria. The study was anchored to the Interest Theory of Human Right. The study adopted Correlational Design. It involved the population of 3211 academic and nonacademic staff of the tertiary educational institutions where 333 participants were drawn using Research Advisor (2006). The researchers employed purposive sampling technique for selecting the state owned tertiary educational institutions and random sampling technique in selection of the participants. The study adapted two instruments: Management of Tortious Liabilities Questionnaire (MTLQ) and Administrative Effectiveness Questionnaire (AEQ) with initial reliability indices of 0.79 and 0.84 respectively and after modification, pilot test was conducted via test-retest method with reliability indices of 0.76 and 0.79 respectively, computed using PPMC. The questionnaires were administered and the data obtained were analysed using frequency, percentages, mean to answer the research questions while, Pearson Product Moment Correlation (PPMC) was used to test the hypothesis. The findings of the study revealed that there is high extent of management of tort of trespass to person in Borno State owned tertiary educational institutions as well as moderate level of administrative effectiveness. And also there is significant positive relationship between management of tort of trespass to person and administrative effectiveness in state owned tertiary educational institutions in Borno State, Nigeria. The researchers recommended frequent training of school heads on effective application of strategies for management of tortious liabilities of trespass to person in schools, among others.